Implementasi Manajemen Pembelajaran Kitab Taisirul Khalaq dalam Upaya Pemahaman Kecerdasan Religius Santri di Pondok Pesantren Hidayatul Mubtadiin Desa Sidoharjo Kecamatan Jati Agung Lampung Selatan Tahun Pelajaran 2023/2024 - M. Ardiansyah; Agus Sujarwo; An An Andari (Journal on Education, 2024)
Learning management is a series of efforts that aim to regulate the teaching and learning process, in order to achieve an effective and efficient teaching and learning process. Religious intelligence can be interpreted as an attitude or behavior that is obedient in implementing religious teachings that are adhered to by tolerance towards practitioners of worship and living in harmony with others. The Book of Taisirul Kholak is a concise book regarding knowledge and morals. This book makes it easier for someone to carry out morals and understand various kinds of morals. So you know exactly what morals must be implemented and what morals must be abandoned. In this thesis, three things are discussed, namely: (1) How to implement the learning management of the book Taisirul Khalaq at the Hidayatul Mubtadiin Islamic boarding school in Jati Agung, South Lampung. (2) What are the efforts to increase the understanding of the religious intelligence of students at the Hidayatul Mubtadiin Islamic boarding school in Jati Agung, South Lampung. (3) What are the Supporting and Inhibiting Factors for the Implementation of learning management of the book Taisirul Khalaq in Efforts to Understand the Religious Intelligence of Santri at the Hidayatul Mubtadiin Islamic boarding school in Jati Agung, South Lampung. The results of comprehensive research regarding the implementation of learning the book of Taisirul Kholaq at the Hidayatul Mubtadiin Islamic boarding school in Jati Agung, South Lampung, can be concluded that: first, the implementation of learning management for the Book of Taisirul Kholaq is running well and effectively as seen from the implementation of effective learning indicators. Second, efforts to understand religious intelligence through learning activities on the book of Taisirul Kholaq at the Hidayatul Mubtadiin Islamic boarding school include: the role of the ustadz of the Book of Taisirul Kholaq in forming students' morals has played an active role, the methods used in forming students' morals are the method of example, example, giving advice, habituation, and punishment.